Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s11255-010-9706-y
|View full text |Cite
|
Sign up to set email alerts
|

An animal model of ischemic priapism and the effects of melatonin on antioxidant enzymes and oxidative injury parameters in rat penis

Abstract: This experimental study was designed to produce ischemia-reperfusion (I/R) injury in rat corpus cavernosum by inducing 1 h of priapism and investigating the effects of melatonin on the levels of oxidative injury parameters. Twenty-one adult male rats were randomly divided into three groups as follows; sham operated, control group (Group C): only penectomy was performed and blood (3 ml) drawn from vena cava inferior (VCI), ischemia and reperfusion group (Group I/R); priapism (1 h) + ½ h reperfusion + penectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Due to the difficulty in exploring these mechanisms in patients, the use of animal models of priapism has become of utmost importance to decipher this devastating clinical challenge [19]. Animal models for priapism include dogs [20, 21], rabbits [22], rats [2327], and mice [2841]. …”
Section: Priapismmentioning
confidence: 99%
“…Due to the difficulty in exploring these mechanisms in patients, the use of animal models of priapism has become of utmost importance to decipher this devastating clinical challenge [19]. Animal models for priapism include dogs [20, 21], rabbits [22], rats [2327], and mice [2841]. …”
Section: Priapismmentioning
confidence: 99%
“…However, whether adenosine is a potential agent which mediates both stroke and priapism needs to be further discussed. Recent studies showed that in corpus cavernosum ischaemia-reperfusion mouse, many oxidative injury parameters like superoxide dismutase (SOD), catalase, malondialdehyde (MDA) and NO in the tissues were all upregulated, and melatonin, which also played neuroprotective actions in stroke,35 could attenuate the activity of SOD and the levels of MDA and NO 36. These conclusions strongly suggested that melatonin may be involved in the stroke-induced priapism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[30], Uluocak et al. [31] and Sanli et al. [32] devised a similar vacuum induced priapism rat model to investigate the medication in preventing priapism induced detrimental effects on erectile tissue.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%
“…Evliyaoglu et al [28,29], Jin et al [30], Uluocak et al [31] and Sanli et al [32] devised a similar vacuum induced priapism rat model to investigate the medication in preventing priapism induced detrimental effects on erectile tissue. The vacuum erectile device (VED) is a cone-tipped standard 50 cc irrigation syringe for Foley urethral catheters [28][29][30]32].…”
Section: Model Established By Vacuum + Constrictor Bandmentioning
confidence: 99%
See 1 more Smart Citation